PENGARUH RASIO Na2SiO3 : NaOH TERHADAP KUAT TEKAN MORTAR GEOPOLIMER BATU NAPAL - Heri Wijaya; vike itteridi; Tarmizi (JURNAL ILMIAH BERING'S, 2021)
This study discusses the use of marl stone as a constituent of geopolymer mortar which aims to determine the effect of the Na₂SiO3 : NaOH ratio to the compressive strength of a marl stone geopolymer mortar. In its manufacture, geopolymer mortar utilizes natural minerals with high SiO2 (silica oxide) content as precursors and uses activators as binders such as NaOH (sodium hydroxide) and Na2SiO3 (sodium silicate), silica oxides contained in these materials will react chemically and form polymer bonds. The method in this study uses an experimental method that is doing direct testing in the laboratory procedures that are carried out in accordance with the stages and planned to refer to the applicable standards. The Na₂SiOi: NaOH activator ratio used in this study is 1, 1.5, and 2. Based on the geopolymer compressive strength test results that have a maximum compressive strength at 28 days with a composition ratio of Na2SiO3: NaOH, 1: 1 for 15 , 07 Mpa. From the results of the analysis it can be concluded that the more use of Na2SiO3, the effect on compressive strength of napal geopolymer stones will decrease. So geopolymer mortar made from stone is included in a simple mortar that is mortar for non-structural parts